Clinico-radiological study in head injury due to road traffic accident caused by stray animals (Asian Journal of Medical Sciences, 2024)
Background: In India, the alarming rise in Road Traffic Accidents (RTAs) is a pressing concern that poses significant threats to public safety and infrastructure.Aims and Objectives: The study was conducted to know the clinico-radiological aspect and associated mortality and morbidity of cases of RTAs caused due to stray animals in central India. Materials and Methods: This current study was a prospective observational study done in the premier institute of central India from April 2023 to July 2023. All RTA patients due to impact with stray animals attending the trauma and neurosurgery department of our institute for 3 months (April 23, 2023–July 30, 2023) were included in the study.Results: A total of 50 patients were recruited for the study. The median age of the patients was 29.00 years (20.00–41.00) (Range). The gender distribution M: F was 38:12. Five (10%) patients reached the T and E within the golden hour (first 1 h). Evening time (42%) was the most common time of accidents (12 PM–6 PM), followed by (6 PM–AM). Analysis of vehicles involved in RTA revealed two-wheelers in 95%, three-wheelers in 3%, and other vehicles in 2% cases. About 34% of total victims were drivers, and 66% were pillion riders or occupants of the vehicle.Conclusion: Our prospective, cross-sectional study aimed to highlight the facts of the increased incidence of RTAs due to stray animals roaming freely on roads, thus adding significant morbidity and costs to society.